Yield Test of Shade-Tolerant Maize Using the Intercropping Method of Maize-Soybean Under Coconut Trees - Dewi, Riska Kurnia; Suliansyah, Irfan; Anwar, Aswaldi; Syarif, Auzar (GoAcademica Research & Publishing, 2024)
Maize is a light-dependent crop, but new varieties have been developed that can tolerate shade. This allows farmers to grow maize as an intercrop between coconut trees, making more efficient use of their land. Farmers can also intercrop with legume plants, which provide additional nitrogen through Rhizobium bacteria, leading to increased maize productivity. The aim of this study was to obtain the best intercropping pattern for maize and soybeans under coconut trees that results high yields in maize. The study was conducted in Padang Pariaman Regency of West Sumatra, at an altitude of approximately 150 meters, from February to July 2022. The experimental design was a Split Plot Design with Randomized Block Design, consisting of three main plot levels (planting time) and four subplot levels (planting model). The results of the study indicate that intercropping maize and soybeans under coconut trees has no effect on the weight of maize cobs, but there is a positive correlation between ear weight, cob length, cob diameter, number of rows per cob, and the weight of 1000 maize seeds.